The Figure of the Minister in Hawthorne's The Scarlet Letter and The Minister's Black Veil - Mohd Nazri, Latiff Azmi; Mutasim Y., Mahadin (2018)
This paper concentrated on was the art of symbolism and allegory in the works of Hawthorne. The paper introduced the two characters as symbolic characters in relation to the symbolic world where they lived. The two ministers were associated with two of the most important symbols in the American literature, the scarlet letter and the black veil. Many interpretations were presented to unveil the ambiguity of the two characters and their emblems. But most of these interpretations revolved in the orbit of the secret sin and the act of repentance or redemption after committing the sin. The scarlet letter and the black veil along with their owners introduced to the readers - as mentioned in the course of the paper - the facts of the incorrectness and duality in the personality of the puritans and the people in general The paper came as a sole effort to introduce two of the greatest works in the history of the American literature The Scarlet Letter and The Minister's Black Veil. The two works played a significant role in projecting truthfully the history of the puritans and their communities in the puritanical New England. The paper attempted also to elevate the reader to the level of symbolism and allegory in the works of Hawthorne and to clarify the ambiguity which associated the two ministers in these works. it is honestly hoped that the paper will present the two works in the most appropriate way and depict to the reader the greatness of Hawthorne as a novelist and a short story writer in the most worthy way.